Simplified patient-specific renal dosimetry in 177Lu therapy: a proof of concept. (December 2021) - Ligonnet, Thomas; Pistone, Daniele; Auditore, Lucrezia; Italiano, Antonio; Amato, Ernesto; Campennì, Alfredo; Schaefer, Niklaus; Boughdad, Sarah; Baldari, Sergio; Gnesin, Silvano
Highlights: Simplified renal dosimetry in 177Lu-PRRT using one SPECT-CT and probe measurements. Proof-of-concept use on experimental phantom and Monte Carlo. Dosimetric method successfully tested on patient images. Abstract: Purpose: The aim of this proof-of-concept study is to propose a simplified personalized kidney dosimetry procedure in 177 Lu peptide receptor radionuclide therapy (PRRT) for neuroendocrine tumors and metastatic prostate cancer. It relies on a single quantitative SPECT/CT acquisition and multiple radiometric measurements executed with a collimated external probe, properly directed on kidneys. Methods: We conducted a phantom study involving external count-rate measurements in an abdominal phantom setup filled with activity concentrations of 99m Tc, reproducing patient-relevant organ effective half-lives occurring in 177 Lu PRRT. GATE Monte Carlo (MC) simulations of the experiment, using 99m Tc and 177 Lu as sources, were performed. Furthermore, we tested this method via MC on a clinical case of 177 Lu-DOTATATE PRRT with SPECT/CT images at three time points (2, 20 and 70 hrs), comparing a simplified kidney dosimetry, employing a single SPECT/CT and probe measurements at three time points, with the complete MC dosimetry. Results: The experimentally estimated kidney half-life with background subtraction applied was compatible within 3% with the expected value. The MC simulations of the phantom study, both with 99m Tc and 177 Lu, confirmed a similar level of accuracy. Concerning the clinical case, the simplified dosimetric method led to a kidney dose estimation compatible with the complete MC dosimetry within 6%, 12% and 2%, using respectively the SPECT/CT at 2, 20 and 70 hrs. Conclusions: The proposed simplified procedure provided a satisfactory accuracy and would reduce the imaging required to derive the kidney absorbed dose to a unique quantitative SPECT/CT, with consequent benefits in terms of clinic workflows and patient comfort.